Studi Kualitatif Efektivitas Komunikasi terhadap Pembentukan Kepribadian Remaja di Daerah Pesisir - Ainiyah, Maslakhatul; Mudlofar, M.; Faqihatin (Jurnal Studi Multidisiplin Qomaruna, 2024)
Adolescence is a crucial developmental phase in a person’s life, during which individuals seek self-identity and understand their social roles. Ineffective communication between parents, teachers, and the social environment with adolescents can significantly impact personality formation, such as reduced self-confidence, a tendency to become introverted, or passive behavior. Communication is a primary tool in social interaction, functioning as a medium for sharing ideas, emotions, and experiences. This study aims to identify the extent to which communication effectiveness influences adolescent personality development and to analyze the supporting and inhibiting factors of communication in the school environment of Tanjung Widoro Village, Mengare. Using a qualitative approach through observation and in-depth interviews, this study found that effective family communication significantly affects adolescents’ behavior and intrapersonal intelligence. Open communication between parents and adolescents fosters a sense of acceptance, courage in decision-making, and the ability of parents to understand and support their children’s development. Supporting factors include parental emotional involvement, consistent communication patterns, and support from the school environment. Conversely, communication barriers arise from a lack of interaction time, generational differences, and social pressures from the surrounding environment. These findings emphasize the importance of effective communication in shaping adolescent personality and provide recommendations to improve communication patterns in family and school environments.